Support Techniques to Enhance Students’ Project-Based Learning - Leong, Siok Je; Tee, Meng Yew (INTI International University, 2011)
The purpose of this study is to investigate the impact of using various support techniques to enhance students’ learning in a project-based diploma level database management course. Project-based learning is a systematic teaching method that engages students in learning essential knowledge and life enhancing skills through o use of authentic quest Ion and carefully structured task. The project was divided into three main phases, involving requirements analysis conceptual design and database system implementation using Microsoft Access. Students were assigned into teams of three to four members based on weak-strong selection techniques. This study was conducted for a period of 12 weeks, guided based on an action research design. The initial findings suggest that techniques such as setting ground rules, regular constructive feedback by the lecturer, using templates to assist thinking, peer-evaluation, questioning and self-reflection can enhance learning.